Experiments in consilience : (Island Press, 2003)
The book describes the work of the Biodiversity Research Network, a team of experts from the United States and Canada brought together to build interdisciplinary connections and stimulate an exchange of expertise. Team members sought to understand the ecology and population dynamics of key species in particular ecosystems, to understand the impact of human populations on those species and ecosystems, and to develop tools and processes for involving a greater variety of stakeholders in conservation efforts.